2020
DOI: 10.1021/acs.jafc.0c00513
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Liquid Chromatography and Metabolomics Analysis of Tannase Metabolism of Gallic Acid and Gallates in Tea Leaves

Abstract: Tannase (E.C. 3.1.1.20) is hypothesized to be involved in the metabolism of gallates and gallic acid (GA) in pu-erh tea fermentation. In this work, we measured tannase in Aspergillus niger fermented tea leaves and confirmed the production of fungal tannase during pu-erh tea fermentation. A decrease in catechin and theaflavin gallates and a significant increase in GA content and the relative peak areas of ethyl gallate, procyanidin A2, procyanidin B2, procyanidin B3, catechin-catechin-catechin, epiafzelechin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Tannase ( E.C. 3.1.1.20 ) secreted by microorganisms is responsible for hydrolyzing gallates into GA in dark teas during microbial fermentation. ,, This could explain the abundant GA in CDTs. In another study, caffeine levels was found to increase significantly after the microbial fermentation of PU tea, and guanine deaminase was reported to have an important relation to the mechanism underlying the increased caffeine content .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tannase ( E.C. 3.1.1.20 ) secreted by microorganisms is responsible for hydrolyzing gallates into GA in dark teas during microbial fermentation. ,, This could explain the abundant GA in CDTs. In another study, caffeine levels was found to increase significantly after the microbial fermentation of PU tea, and guanine deaminase was reported to have an important relation to the mechanism underlying the increased caffeine content .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 569 metabolites were identified by comparing with standards from the MetWare selfconstructed metabolite database and MS/MS spectrum information from published databases (MassBank, KNAp-SAcK, HMDB, and METLIN). All the identified metabolites, as listed in detail in Table S1, were classified into 10 subgroups pointing to their metabolic pathways, including flavonoids (185), phenolic acids (84), amino acids and derivatives (62), lipids (54), others (50), nucleotides and derivatives (42), organic acids (31), alkaloids (19), tannins (19), and lignans and coumarins (12). Successively, all metabolites were subjected to multivariate statistical analysis.…”
Section: Comparison Of the Levels Of Major Chemicalmentioning
confidence: 99%
“…In this study, SF3 and CK3 were selected and delivered to the company for determination the nVFCs of samples by ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) analysis (Shanghai Meiji Biomedical Technology Co., Ltd., Shanghai, China). The following works were accomplished according to our recent study, which included the extraction of nVFCs, UPLC separation, ESI-MS/MS monitoring, and data processing (Liu et al, 2020). Identification of nVFC was dependent on the primary and secondary MS data, annotated against an in-house database, or the matches of both retention times and MS data to some standard compounds in Metware.…”
Section: Nvfc Analysismentioning
confidence: 99%
“…Metabolomics employs different analytical platforms including high-performance liquid chromatography (HPLC) [22][23][24][25][26][27], Fourier transformed infrared (FT-IR) spectroscopy [28][29][30][31], mass spectrometry (MS) [32][33][34][35] and nuclear magnetic resonance (NMR) spectroscopy [36][37][38][39][40][41][42].…”
Section: Metabolomics Analytical Toolsmentioning
confidence: 99%